Os meus colegas bebem álcool? Consumo de álcool e percepção do consumo em adolescentes - estudo realizado com estudantes do 3º ciclo de escolas públicas de Coimbra - Barroso, Teresa (2010)
International studies have consistently demonstrated that adolescents overestimate peer alcohol consumption and that this misperception is predictive of individual consumption. This study was developed in order to characterise alcohol consumption and the perception of peer consumption of adolescents from state-run middle schools in the city of Coimbra. It was used to improve a programme for the prevention of alcohol use/abuse. The sample included 654 adolescents (51.5% female gender). The results demonstrated a clear overestimation of the perception of peer consumption. Older adolescents, with experience of consumption and/or intoxication, have a tendency to present a high level of perception of peer consumption. No gender differences were registered. These results consolidate the importance of integrating the correction of the perceptions regarding peer consumption into programmes of prevention of alcohol use/abuse.